Two new species of Amnestus from Guatemala, with new records for some other Guatemalan burrower bugs (Hemiptera: Heteroptera: Cydnidae) - M., Cristina Mayorga; P., Luis Cervantes (Zootaxa, 2009)
In this paper we describe two new species in the genus Amnestus, Amnestus henryi and Amnestus zacki, and we register new localities for 10 species of burrowing bugs for the fauna of Guatemala; two of these species correspond to new records, Amnestus pusio (Stål), and Dallasiellus reflexus Froeschner. We include a brief description of the 28 species known for Guatemala, mentioning old and new records; new species are fully described and illustrated, and drawings of the male genitalia, scent gland opening, fore, and hind legs of males are also presented. A key to separate the 28 Guatemalan species of burrower bugs is provided.